Ultrastructure of egg membrane of rohu (Labeo rohita) - Gopalakrishnan, A; Ponniah, A G; Lal, Kuldeep K (Indian Journal of Fisheries, 2011)
The fine structure of the egg envelope and micropyle of unfertilised spawnedeggs of rohu (Labeo rohita) was observed using scanning electron microscope(SEM). The outer surface showed regularly arranged pores (dia. 0.20 - 0.25 Î¼m)but was devoid of any filaments, fibrils or wrinkles. The micropyle was funnelshaped which exibited an outer pit (10 Î¼m dia.) narrowing into a distinct canal(4.5 Î¼m dia.). The larger diameter of the micropylar canal in comparison withthe sperm head size of rohu and some other cyprinids make intergeneric andinterspecific hybridisation easy in rohu.